Lactic acid bacteria bacteriocins as novel antimicrobials against antibiotic-resistant Streptococcus pneumoniae in opthalamic infections - Marriam Wasif; Nazish Mazhar Ali; Syed Abdullah Mazhar; Sher Muhammad Zaman; Seher kiran; Maham Chaudhry; Ibtissem Louiz; Amor Hedfi; Manel Ben Ali; Arslan Muhammad Ali Khan; Itrat Zahra (Molecular Biology Reports, 2026)

Genome sequencing reveals genes under selection for olfactory transduction in highland sheep - Anees Ahmad; Muhammad Ibrahim; Muhammad Yaqoob; Muhammad Fahim; Sher Hayat Khan; Israr Ud Din; Majid Khan; Sohail Ahmad (Molecular Genetics and Genomics, 2026)
Kutta is an indigenous sheep breed found in the mountainous region of Swat, Pakistan. In this study we evaluated the performance of Kutta sheep within their natural habitat and identified genomic regions associated with environmental adaptability using whole genome sequencing. Flocks are mostly managed under a transhumant production system with year-round breeding. Kutta sheep demonstrated higher lambing efficiency under the available resources. Although the body size of rams and ewes was comparable, significant variation was observed among different age groups. Whole genome sequencing identified 15.46 million variants relative to Oar_v1.0 reference genome assembly. Exonic variants accounted for 2.3% of all protein coding gene variants and affected 6347 genes. These genes were primarily enriched in pathways related to G protein-coupled receptor signaling (700 genes) and olfactory transduction (500 genes). Selective sweep analysis detected 1930 genes within the regions of high homozygosity across the genome. Based on homozygosity patterns, biological relevance, and colocalization with known QTLs, 11 candidate genes were identified as putative selective signature. Five of these genes (OR4C6L, OR1086L, OR5AK2L, QR5T2L, OR9Q2) belonged to the olfactory receptor family. These olfactory receptor genes may contribute to high-altitude adaptation in Kutta sheep by enhancing their ability to locate food resources, recognize mates, and detect predators in challenging mountainous environments. Further screening of the OR4C6L sequence across 12 indigenous sheep breeds revealed marked differences between highland and lowland populations. Collectively, these findings provide comprehensive genomic insights into high-altitude adaptation of sheep and highlight the potential role of olfactory perception in survival and environmental fitness.

Genome-wide study uncovering the role of GPAT gene family in watermelon and functional validation of ClGPAT8 against cold stress - Ali Aslam; Xiaomeng Wang; Muhammad Waseem; Muhammad Azam; Ashir Masroor; Qinghua Shi; Sher Muhammad; Aseel Smerat; Muhammad Khuram Razzaq; Ruimin Zhang (Plant Science, 2026)

Mechanistic evaluation of electrocoagulation pre-treatment for reducing calcium–magnesium scaling during non-oily refinery wastewater treatment - Kanwal Anwar; Muhammad Saqib Nawaz; Sher Jamal Khan; Noreddine Ghaffour; Momina Maheen (Journal of Environmental Chemical Engineering, 2026)

Retraction notice to “Polyvinyl alcohol and aminated cellulose nanocrystal membranes with improved interfacial compatibility for environmental applications” [Environ. Res. 214 (2022) 113793] - Saleem Ahmad; Zaib Jahan; Farooq Sher; Muhammad Bilal Khan Niazi; Tayyaba Noor; Honghao Hou; Ofaira Azhar; Emina Karahmet Sher (Environmental Research, 2026)

Reversible -NH2/-NH3+ switching drives proton-coupled electron transfer for selective CO2-to-CO photoreduction in S-scheme MOF/g-C3N4 heterojunction - Sharafat Ali; Sher Ali; Ahmed Ismail; Yong Wang; Syed Ul Hasnain Bakhtiar; Qaisar Alam; Pir Muhammad Ismail; Wajid Ali; Ahmad Iqbal; Polycarpos Falaras; Jiabao Yi; Fazal Raziq; et al. (Chemical Engineering Journal, 2026)

Lactiplantibacillus plantarum AS21 Reduces Colitis in Mice by Modulating Inflammation, Gut Barrier Function, and Microbiota in an Intervention Dose and Time-dependent Manner - Ali Sher Bacha; Mengyan Chen; Zitong Ding; Mengya Jia; Hu Chen; Ikram Khan; Muhammad Ishaq; Azmat Ullah Jan; Ashiq Khan; Xusheng Guo (Probiotics and Antimicrobial Proteins, 2026)

Bifidobacterium animalis subsp. lactis and Enterococcus hirae Enhance Immunity by Modulating Gut Microbiota and Metabolic Pathways in Immunosuppressed Mice - Azmat Ullah Jan; Hu Chen; Muhammad Ishaq; Mengya Jia; Ali Sher Bacha; Qiang Li; Mengyan Chen; Zitong Ding; Xusheng Guo (Probiotics and Antimicrobial Proteins, 2026)

Bifurcation and chaos design of radial basis neural network for predictive modeling of fractional double-strain HIV co-infection model with intercellular delays and stochastic effects - Muhammad Wajahat Anjum; Noreen Sher Akbar; M. Bilal Habib; A. Alzubaidi; S. Saleem (Theory in Biosciences, 2026)

Erratum to: Bifidobacterium animalis subsp. lactis and Enterococcus hirae Enhance Immunity by Modulating Gut Microbiota and Metabolic Pathways in Immunosuppressed Mice - Azmat Ullah Jan; Hu Chen; Muhammad Ishaq; Mengya Jia; Ali Sher Bacha; Qiang Li; Mengyan Chen; Zitong Ding; Xusheng Guo (Probiotics and Antimicrobial Proteins, 2026)

Tailoring strontium-nickel supported reduced graphene oxide nanostructure for synergistic catalytic hydrogen generation from sodium borohydride and photodegradation of organic pollutant - Rana Nauman Hassan; Faryal Ali; Shoaib Akhtar; Abu Bakar Siddique; Khaled Fahmy Fawy; Muhammad Sher; Muhammad Ashraf Shaheen; Muhammad Fayyaz ur Rehman; Umar Nishan; Tauqeer Ahmad; Arshad Ali; Azhar Abbas (Fuel, 2026)

Regional cryosphere strategy for the Hindu Kush Himalaya - Sher Muhammad; Mohd. Farooq Azam; Miriam Jackson; Qianggong Zhang (Journal of Mountain Science, 2026)
The Hindu Kush Himalaya (HKH) hosts the largest concentration of glaciers, seasonal snow, and permafrost outside the polar regions. Ongoing climate change has accelerated glacier mass loss, reduced snow cover, degraded permafrost, and altered runoff seasonality. These changes have amplified multihazard risks such as glacial lake outburst floods, avalanches, and landslides, with cascading impacts on water, energy, food, ecosystems, and livelihoods. Yet, field monitoring remains sparse, fragmented, and uneven across the region with limited long-term records and minimal data sharing. This perspective presents a Regional Cryosphere Strategy (RCS) for the HKH that responds to these deficits by: (i) consolidating and institutionalising standardised monitoring of glaciers, snow, and permafrost; (ii) building sustained capacity through specialised regional capacity-building activities, fellowships, and shared instrumentation with priority given to a Gender Equality and Social Inclusion (GESI) framework; (iii) establishing a Regional HKH CryoHub to ensure Findable, Accessible, Interoperable, and Reusable (FAIR) and policy-relevant data and knowledge services; and (iv) prioritising operational decision-support services such as the HKH seasonal Snow Watch for water and energy planning, hazard monitoring and early warning systems, and basin-scale assessments that link cryosphere trends to risks for people and infrastructure. This strategy is designed to align HKH observations and services with global initiatives, ensuring that regional data streams inform global assessments while countries can access technical and financial support mechanisms. We argue that a basin-representative, quality-assured, and interoperable cryosphere observation and services system can strengthen regional resilience, reduce risks, and amplify the HKH voice in global climate dialogues.

Glacial lake expansion and outburst flood threat along the China–Pakistan Economic Corridor: Hunza Basin, Pakistan (1990–2021) - Saddique Akbar; Junbo Wang; Atta Ullah; Sher Muhammad (Journal of Mountain Science, 2026)

Advancements in Wheat Rust Resistance through Molecular and Field-Based Approaches - Muhammad Waheed Riaz; Dehua Wang; Shams ur Rehman; Yufeng Zhang; Faheem Tariq; Alam Sher; Shabbir Hussain; Muhammad Aamir Manzoor; Abdul Raziq; Zhiying Deng (Journal of Soil Science and Plant Nutrition, 2026)

Climate driven drought risk and machine learning approaches for urban resilience and sustainable water governance - Shan-e-hyder Soomro; Huaibin Wei; Muhammad Waseem Boota; Nishan-E-Hyder Soomro; Sher Ali; Sana Nazli; Caihong Hu; Jiali Guo (Environmental Research, 2026)

Host–Microbiota Metabolic Interactions in Atherosclerosis: Oral, gut, and Blood Perspectives - Ikram Khan; Muhammad Irfan; Ali Sher Bacha; Imran Khan; Yasir Ali; Zhiqiang Li (Probiotics and Antimicrobial Proteins, 2026)

Pangenome-assisted characterization of TaBAM genes and association of TaBAM16-1B with NDVI in wheat - Maira Anam; Zulqurnain Khan; Muhammad Ali Sher; Muhammad Sajjad; Muhammad Kashif Naeem; Zijin Zhang; Sania Javeed; Fatima Javeria; Jing Chen; Shoaib Ur Rehman (Theoretical and Applied Genetics, 2026)

Deep learning-based classification of nitrate and nitrite concentrations from water samples using colorimetric test strip images - Muhammad Roman; Mazhar Sher; Chamika Kuruppuarachchi; Arshid Ali; Chulwoo Pack; Azlan Zahid; Ali Mirzakhani Nafchi (Environmental Monitoring and Assessment, 2026)
Accurate monitoring of nitrate and nitrite concentrations in water is essential for sustainable agriculture, safeguarding public health, and protecting aquatic ecosystems from nutrient pollution. Traditional methods for detecting nitrate and nitrite in water samples are precise but costly, complex, and time-consuming, limiting their practicality for frequent on-site testing. This research proposes deep learning-based computer vision techniques to classify nitrate and nitrite concentrations using images of colorimetric test strips. An RGB IMX219 camera was used to acquire images of colorimetric test strips under standardized, controlled illumination conditions to ensure consistent image quality. A total of 1938 nitrate images and 1190 nitrite images were collected before augmentation. After preprocessing and training-only data augmentation, both classical machine learning baselines based on hand-crafted color and texture features and deep learning models—including a multilayer perceptron (MLP) and convolutional neural networks (AlexNet, VGG16, ResNet18, and GoogLeNet)—were trained and evaluated using an independent test set and stratified fivefold cross-validation. For nitrate classification, ResNet18 and GoogLeNet achieved near-perfect 100% test accuracy, with mean cross-validation accuracy of 99.97% ± 0.04%, substantially outperforming classical baseline models based on hand-crafted color and texture features, which achieved at most 83.5% test accuracy. For nitrite classification, GoogLeNet achieved the strongest overall performance, with a test accuracy of 97.48% and a fivefold cross-validation accuracy of 95.22% ± 1.17%, substantially outperforming the best classical baseline model, which achieved a maximum test accuracy of 83.19%. These results demonstrate that deep CNN-based feature learning provides a significant performance advantage over simpler methods under controlled imaging conditions, supporting the suitability of the proposed system for rapid, image-based water quality assessment and motivating future evaluation under broader real-world deployment scenarios.

Individual and combined decontamination effect of aqueous ozone and plant extracts on fungi and aflatoxins in brown rice - Iqra Naeem; Amir Ismail; Yun Yun Gong; Muhammad Riaz; Muhammad Arif Shahzad; Aneela Hameed; Mubashir Aziz; Asif Mahmood; Waheed Al Masry; Muhammad Latif; Sher Ali; Carlos A.F. Oliveira (Food Control, 2026)

Development of an AI-Enabled Vision-Based On-Site Rapid Detection of Nitrates and Nitrites from Drainage Samples - Muhammad Roman; Azlan Zahid; Ali Mirzakhani Nafchi; Mazhar Sher (Water, Air, & Soil Pollution, 2026)
Plant growth is significantly impacted by the concentration of nutrients in the soil. Accurate and real-time measurement of nitrates and nitrites levels remains a significant challenge. Existing laboratory-based methods are expensive, time-consuming, and labor-intensive, highlighting the need for a rapid, on-site solution. This study proposes a rapid method for measuring nitrates and nitrite levels in water samples collected from tile drainage. We utilized Hach Nitrate and Nitrite test strips for image dataset collection as these test strips change color based on the concentration of nitrate and nitrite in the water samples. A purpose-built black box, equipped with an internal lighting arrangement for imaging test strips, was designed to collect images of the test strips. Unlike many existing smartphone-based colorimetric approaches, which are sensitive to ambient lighting variations and often rely on external calibration or offline analysis, the proposed system integrates a controlled illumination environment with real-time edge computation for robust on-site detection of nitrate and nitrite. An Nvidia Orin Nano module, connected with an IMX219 camera sensor, was used to capture images of the test strips. Image preprocessing was performed, followed by the implementation of a VGG16-based network for feature extraction. A dataset of approximately 3128 images spanning multiple nitrate and nitrite concentration levels was collected under controlled imaging conditions. Multiple machine learning models including logistic regression (LR), support vector machines (SVM), k-nearest neighbors (KNN), naïve Bayes (NB), and random forest (RF) were evaluated for classification. The nitrate detection using KNN achieved an accuracy of 99.96% training, 99.92% testing, and 99.79% cross-validation. For nitrite detection, the SVM model achieved accuracy of 99.02%, 98.04%, and 98.07% for training, testing, and cross-validation, respectively, demonstrating both systems' high reliability and practical applicability for real-time monitoring. The total system cost is approximately USD 300, highlighting the affordability and practicality of the proposed solution for on-site water quality monitoring. This technology can enable farmers, water quality researchers, and agronomists to efficiently monitor the levels of nitrates and nitrites in tile drainage samples, enabling data-driven decisions to maximize crop yields.

First Report on Phytochemical Profiling and Biological Activities of Anthemis cotula L. Flowers - Saqib Ullah; Muhammad Aaqil Khan; Afnan M. Alnajeebi; Faten Zubair Filimban; Faisal Alsenani; Sher Wali (Journal of Pharmaceutical Innovation, 2026)

Retraction Note: Morphological and genetic diversity of barley (Hordeum vulgare L.) germplasm - Ayaz Ali; Rahman Ullah; Saeed Anwar; Ahmad Ali; Zahid Ullah; Hassan Sher; Javed Iqbal; Banzeer Ahsan Abbasi; Dunia A. Al Farraj; Mohamed S. Elshikh; Muhammad Qasim; Rashid Iqbal (Genetic Resources and Crop Evolution, 2026)

Potential Application of NADPH-Dependent FMN Reductase-Harboring Delftia Acidovorans in Laboratory-Scale Textile Wastewater Treatment and Re-Use - Awais Maqsood; Syeda Khola Tazeen; Sabir Hussain; Faisal Mahmood; Sher Muhammad; Muhammad Shafiq Shahid; Faizah Amer Altihani; Mohamed Hashem; Danish Riaz; Irfan Manzoor; Muhammad Shahid (Water, Air, & Soil Pollution, 2026)

Synergistic Particle Swarm Optimized Bio-inspired Artificial Neural Network for Fractional Analysis of tumor-immune competitive system with multiple time delays - Muhammad Wajahat Anjum; Noreen Sher Akbar; Muhammad Bilal Habib; Taseer Muhammad (Swarm and Evolutionary Computation, 2026)

Synergistic Effects of Multi-walled Carbon Nanotubes and Plant Growth Regulators on In Vitro Morphogenesis of Sugarcane (Saccharum spp. L.) - Aneela Iqbal; Raham Sher Khan; Karim Gul; Muhammad Aizaz; Mohammad Tahir; Hazir Rahman; Douglas Law; Ayaz Ahmad (Sugar Tech, 2026)

Developing a RUSLE-Based Tool for Analyzing Climate Induced Soil Erosion and Reservoir Sedimentation in the Tarbela Region - Muhammad Arif Goheer; Sher Shah Hassan; Syeda Rosheen Raza Kazmi; Muhammad Taimoor Ashfaq Malik; Syed Zee Ali Shan (International Journal of Environmental Research, 2026)

Truncated Variants in FAM20A and WDR72 Genes Underlie Autosomal Recessive Amelogenesis Imperfecta in Four Pakistani Families - Sadaqat Ullah; Sher Alam Khan; Samin Jan; Salah Ud Din; Nazif Muhammad; Zia Ur Rehman; Abid Jan; Muhammad Tariq; Noor Muhammad; Abdul Ghani; Naveed Wasif; Saadullah Khan (Biochemical Genetics, 2026)
Amelogenesis Imperfecta (AI) is a set of hereditary diseases affecting enamel development, leading to various types of enamel defects, potentially impacting oral health unassociated with other generalized defects. AI manifests in syndromic and non-syndromic forms and can be inherited through autosomal recessive, autosomal dominant, or X-linked inheritance patterns. Genetic studies have identified sequence variants in a number of genes (≥ 70) linked to both syndromic and non-syndromic AI, highlighting the genetic diversity underlying the condition. The current study involved clinical evaluation and exome sequencing, aimed at identifying the causative variants in four unrelated consanguineous Pakistani families presenting AI phenotypes. The exome sequencing results revealed a novel homozygous frameshift variant FAM20A : NM_017565.4, c.188dupA; p.(Asp63Glufs*17) in families A, B, and C while a nonsense homozygous variant WDR72 : NM_182758.4, c.2686C > T; p. (Arg896*) in family D. The segregation of both variants was confirmed by Sanger sequencing. Bioinformatics analysis predicted the pathogenicity of these genetic variants. These alterations suggest functional consequences, potentially impairing the FAM20A and WDR72 proteins and causing dental anomalies. This investigation significantly broadens our understanding of FAM20A and WDR72 ’s involvement in AI. Furthermore, this study highlights the genetic heterogeneity of AI (involving FAM20A and WDR72 in this study) within the Pakistani population.

Electron-rich sulfur sites and dual interfacial bonds in S-scheme heterojunction enable high quantum yield and stable hydrogen production - Sharafat Ali; Sajjad Ali; Shu-Long Li; Ahmed Ismail; Sher Ali; Pir Muhammad Ismail; Syed Ul Hasnain Bakhtiar; Fazal Raziq; Mohammad Z. Rahman; Liang Qiao (Chemical Engineering Journal, 2026)

Genetic and morphological data indicate the occurrence of a Rhipicephalus sp. and the absence of Rhipicephalus linnaei in Pakistan - Muhammad Numan; Zaibullah Khan; Sher Bahadar Khan; Mohibullah Shah; Iram Liaqat; Itabajara da Silva Vaz Junior; Lidia Chitimia-Dobler; Abid Ali; Zhihua Sun; Mashal M. Almutairi (Tropical Animal Health and Production, 2026)

Transition of the Karakoram anomaly under emerging hydroclimatic trends - Yasir Latif; Sara C. Pryor; Sardar Ateeq-Ur-Rehman; Sher Muhammad; Muhammad Yaseen; Muhammad Atif Wazir (Science of The Total Environment, 2025)

The potential influence of food additives and contaminants on the gut microbiota: A comprehensive review - Sana Ullah; Sher Ali; Muhammad Atif; Muhib Ullah; Ghulam Nabi; Lucas Gabriel Dionisio Freire; Eliana Setsuko Kamimura; Amir Sasan Mozaffari Nejad; Carlos Augusto Fernandes de Oliveira (Food and Chemical Toxicology, 2025)

Mixed convective heat transfer enhancement in hybrid nanofluid flow through complex-finned tube cavities - Noreen Sher Akbar; Salman Akhtar; Shakil Shaiq; Muhammad Fiaz Hussain; Taseer Muhammad; M. Farooq; M. Bilal Habib (Dynamics of Atmospheres and Oceans, 2025)

Computational study of thermal effects on squeezing flow of water based ( Ti O 2 − Zn ) hybrid nanofluid in a parallel plates for microelectronics dispersal - Mazhar Hussain; Sadia Hameed; Noreen Sher Akbar; Taseer Muhammad (Dynamics of Atmospheres and Oceans, 2025)

High accuracy computational approach to study Casson hybrid nanofluid flow under induced magnetic field inside wavy walls configuration having peristaltic motion with entropy generation - Noreen Sher Akbar; Javaria Akram; S. Ijaz; Zaib Jahan; Taseer Muhammad; Muhammad Bilal Habib; M. Fiaz Hussain; M. Farooq (Dynamics of Atmospheres and Oceans, 2025)

Carbon Nanotubes Improve Quantitative and Qualitative Attributes of Potato (Solanum tuberosum L) Genotypes - Muhammad Ismail; Muhammad Imtiaz; Raham Sher Khan; Fazal Jalal; Fazal Said; Muhammad Ali Khan; Syed Hussain; Badshah Islam; Salman Khan; Sabir Khan; Atta Ullah; Maqsood Khan; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Prediction of RNA editing sites and genome-wide characterization and identification of PERK gene family in Oryza sativa in response to salinity stress - Hafiz Muhammad Waqas; Muhammad Abu Bakar Saddique; Sajid Fiaz; Afnan A. Alnufaei; Muhammad Ali Sher; Badr Alharthi; Muhammad Hammad Nadeem Tahir; Mahmood Alam Khan; Shahmeer Shahid; Seung Hwan Yang (Genetic Resources and Crop Evolution, 2025)

FinTech, environmental innovation, and social capital drive environmental and economic development in Asia - Yun Li; Muhammad Naeem Shahid; Muhammad Umar Islam; Muhammad Ishtiaq; Falak Sher (Environment, Development and Sustainability, 2025)

Aspergillus spp and aflatoxins in Pakistani rice: A case study on the decontamination effect of accelerated aging and improved storage practices - Iqra Naeem; Amir Ismail; Yun Yun Gong; Muhammad Riaz; Aneela Hameed; Mubashir Aziz; Asif Mahmood; Waheed Al Masry; Muhammad Latif; Sher Ali; Carlos Augusto Fernandes de Oliveira (Toxicon, 2025)

Emission characteristics of a compression ignition engine using biodiesel and clove oil antioxidant blends - Sher Muhammad Ghotto; Sajjad Bhangwar; Ramez Raja; Muhammad Kashif Abbasi; Gordhan Das Valasai; Muhammad Ramzan Luhur; Stefano Landini (Biomass and Bioenergy, 2025)

Structure-guided drug repurposing and dynamics simulation reveal anti-viral candidates for Bourbon virus - Israr Hussain; Itazaz Ul Haq; Muhammad Rahiyab; Junaid Khan; Rooh Ullah; Syed Shujait Ali; Hassan Sher; Arshad Iqbal (In Silico Pharmacology, 2025)

Correction: Interactive Effect of Genotype and Zinc Sulphate Improves Productivity and Grain Biofortification of Bread Wheat in Alkaline Soils - Sami Ul‑Allah; Farrukh Azeem; Ahad Madani; Ahmad Sher; Abdul Sattar; Muhammad Ijaz; Mojtaba Hassanzadehdelouei; Asad Azeem; Waqas Malik (Journal of Soil Science and Plant Nutrition, 2025)

Isolation, biochemical characterization, and antimicrobial activities of EPS-producing bacterial endophytes from Moringa oleifera - Karim Gul; Raham Sher Khan; Aneela Iqbal; Atta Ullah; Syed Muhammad Shafi Shah; Anwar Hussain; Douglas Law; Ayaz Ahmad; Salimullah Khan (Folia Microbiologica, 2025)

Flood susceptibility assessment and mapping using GIS-based analytical hierarchy process and frequency ratio models - Saad Ashfaq; Muhammad Tufail; Asif Niaz; Sher Muhammad; Hassan Alzahrani; Aqil Tariq (Global and Planetary Change, 2025)

Integrated groundwater quality assessment using GIS and statistical analysis techniques at Islamkot subdistrict in the Thar desert area - Imran Aziz Tunio; Sheeraz Ahmed Memon; Love Kumar; Habibullah Abbasi; Habib Ursani; Sher Muhammad Ghoto (Groundwater for Sustainable Development, 2025)

Efficacy of Flumetsulam for Post-Emergence Weed Management in Chickpea (Cicer Arietinum L.) Under the Semi-Arid Region of Pakistan - Muhammad Khuram Razzaq; Ali Aziz; Faisal Hayat; Muhammad Zia Ul Haq; Irfan Rasool; Muhammad Naveed Babur; Ali Aslam; Sher Muhammad; Ammara Tahir; Khalid Hussain (Journal of Crop Health, 2025)

An overview of ethnobotanical investigations for primary healthcare: a case study from Mardan district, Pakistan - Muhammad Mohsin; Musheerul Hassan; Ivana Vitasović-Kosić; Mona S. Alwahibi; Sher Wali; Qoryog’diyev Zufar Oxunjonovich; Muhammad Abdul Aziz; M. Ajmal Ali; Rainer W. Bussmann; Arshad Mehmood Abbasi (Plant Biosystems, 2025)

Alkali-activation of copper slag: Characterization and mechanical properties of inorganic polymer binder - Dhiraj Surendra Mahajan; Sher Singh Meena; Salman Muhammad (Chemical Engineering Journal, 2025)

Mapping mangroves land suitability using machine learning and MCDM in the Indus Delta, Pakistan - Sher Shah Hassan; Muhammad Ajmal; Muhammad Arif Goheer; Zainab Ali; Muhammad Suleman (Theoretical and Applied Climatology, 2025)

Dual colorimetric sensing of Hg(II) and Fe(III) using sulfanilamide-stabilized silver nanoparticles and evaluating their photodegradation and antibacterial properties - Maria Kanwal; Muhammad Sher; Azhar Abbas; Shoaib Akhtar; Abu Bakar Siddique; Muhammad Naeem ul Hasan; Nasir Assad; Hassan A. Alhazmi; Hatem M.A. Amin (Journal of Water Process Engineering, 2025)

Tailoring g-C3N4 properties through P and K co-doping: advancing photocatalytic CO2 reduction to CH4 - Ahmed Ismail; Muhammad Zahid; Bilal Ahmad; Salman Hayat; Sher Ali; Syed ul Hasnain Bakhtiar; Abdullah N. Alodhayb; Xiaoqiang Wu; Qaisar Alam; Sharafat Ali; Liang Qiao (Chemical Engineering Journal, 2025)

Interesterification of waste cooking oil via microwave irradiation for glycerol-free biodiesel production - Muhammad Umer Qadeer; Muhammad Ayoub; Muhammad Hamza Nazir; Muhammad Asad Javed; Zulqarnain; Imtisal Zahid; Mariam Ameen; Farooq Sher; Alhassan Ibrahim (Biomass and Bioenergy, 2025)

Interactive Effect of Genotype and Zinc Sulphate Improves Productivity and Grain Biofortification of Bread Wheat in Alkaline Soils - Sami Ul-Allah; Farrukh Azeem; Ahad Madani; Ahmad Sher; Abdul Sattar; Muhammad Ijaz; Mojtaba Hassanzadehdelouei; Asad Azeem; Waqas Malik (Journal of Soil Science and Plant Nutrition, 2025)

Occurrence of aflatoxins and effect of preventive practices to inhibit fungal growth and aflatoxin production in leftover flat bread/chapati used as animal feed and stored in Pakistani dairy farms - Mavra Amin; Amir Ismail; Iqra Naeem; Usama Nasir; Muhammad Riaz; Yun Yun Gong; Sher Ali; Michael N. Routledge; Amna Iqbal; Asifa Saif; Carlos Augusto Fernandes Oliveira (Journal of Stored Products Research, 2025)

Diffused sunlight assisted green synthesis of silver nanoparticles using Cotoneaster nummularia polar extract for antimicrobial and wound healing applications - Nasir Assad; Muhammad Naeem-ul-Hassan; Muhammad Ajaz Hussain; Azhar Abbas; Muhammad Sher; Gulzar Muhammad; Yasir Assad; Muhammad Farid-ul-Haq (Natural Product Research, 2025)

Association mapping of leaf rust disease resistance and yield related traits in bread wheat using a high density 90K SNP array - Muhammad Rauf Shah; Muhammad Ali Sher; Salma Bashir; Muhammad Zeshan Zafer; Douglas Law; Sania Begum; Nasr Ullah Khan; Mohamed Farouk Elsadek; Khalid S. Al-Numair; Daniel K. Y. Tan; Muhammad Yasin (Journal of Plant Diseases and Protection, 2025)

Geospatial assessment of climate variability and drought patterns: a case study from Pakistan - Sher Shah Hassan; Muhammad Arif Goheer; Humera Farah; Faiza Hafeez; Khurram Sheraz; Javaria Fahad; Aqil Tariq (Theoretical and Applied Climatology, 2025)

RETRACTED ARTICLE: ArticleNoteMorphological and genetic diversity of barley (Hordeum vulgare L.) germplasm - Ayaz Ali; Rahman Ullah; Saeed Anwar; Ahmad Ali; Zahid Ullah; Hassan Sher; Javed Iqbal; Banzeer Ahsan Abbasi; Dunia A. Al Farraj; Mohamed S. Elshikh; Muhammad Qasim; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

Heavy metals pollution in riverine sediments: Distribution, source, and environmental implications - Kifayatullah Khan; Muhammad Younas; Muhammad Yaseen; Hassan Sher; Afsheen Maryam; Sobhy M. Ibrahim; Adnan Adnan; Ahmad Ali; Muhammad Fawad; Akhtar Zeb Khan; Nasrullah Khan; Izaz Ali Shah (Environmental Monitoring and Assessment, 2025)

Novel mutations in exon 2 of follistatin (FST) gene associated with wool fiber diameter in sheep - Tahira Mir; Muhammad Ibrahim; Muhammad Siraj; Sajid Ali Khan Bangash; Sher Hayat Khan; Majid Khan; Muhammad Tayyab; Sohail Ahmad (Small Ruminant Research, 2025)

Harmonizing traditional and biotechnological approaches to engineer crop microbiomes: Enhancing resilience optimization - Muhammad Siddique Afridi; Abdul salam; Sher Ali; Sumaira; Willian César Terra; Baber Ali; Muhammad Atif Muneer; Gustavo Santoyo (Biocatalysis and Agricultural Biotechnology, 2024)

Insights Into the Morphological Analysis, Phytochemical Profile and Antimicrobial Activities of the Multi-Walled Carbon Nanotubes-Induced In Vitro Sugarcane - Aneela Iqbal; Muhammad Usman; Karim Gul; Atta Ullah; Syed Muhammad Shafi Shah; Hazir Rahman; Raham Sher Khan (Sugar Tech, 2024)

An SNP based genotyping assay for genes associated with drought tolerance in bread wheat - Abdul Rauf; Muhammad Ali Sher; Umar Farooq; Awais Rasheed; Muhammad Sajjad; Ruilian Jing; Zulqurnain Khan; KOTB A. Attia; Arif Ahmed Mohammed; Sajid Fiaz; Jing Chen; Shoaib Ur Rehman (Molecular Biology Reports, 2024)

Nanoparticles in plant resistance against bacterial pathogens: current status and future prospects - Maria Gul; Raham Sher Khan; Zia Ul Islam; Sumayya Khan; Amina Shumaila; Sidra Umar; Sajad Khan; Brekhna; Muhammad Zahoor; Allah Ditta (Molecular Biology Reports, 2024)

Flexible temperature and humidity sensors of plants for precision agriculture: Current challenges and future roadmap - Muhammad Ikram; Sikander Ameer; Fnu Kulsoom; Mazhar Sher; Ashfaq Ahmad; Azlan Zahid; Young Chang (Computers and Electronics in Agriculture, 2024)

Greenly synthesized zinc oxide nanoparticles: An efficient, cost-effective catalyst for dehydrogenation of formic acid and with improved antioxidant and phyto-toxic properties - Sami Ullah; Muhammad Shaban; Abu Bakar Siddique; Anam Zulfiqar; Naveed Shahzad Lali; Muhammad Naeem-ul-Hassan; Muhammad Imran Irfan; Muhammad Sher; Muhammad Fayyaz ur Rehman; Ali Hanbashi; Fahad Y. Sabei; Hatem M.A. Amin; et al. (Journal of Environmental Chemical Engineering, 2024)

From lake to fisheries: Interactive effect of climate and landuse changes hit on lake fish catch? - Shan-e-hyder Soomro; Muhammad Waseem Boota; Haider M. Zwain; Majid Rasta; Caihong Hu; Chengshuai Liu; Yinghai Li; Ao li; Jijun Chen; Chunyun Zhu; Sher Ali; Jiali Guo; et al. (Environmental Research, 2024)

Integrated Application of Micronutrients Improves Productivity and Seed Quality of Canola Crop under Conventional Tillage System - Muhammad Ijaz; Shahbaz Khan; Sami Ul-Allah; Abdul Sattar; Ahmad Sher; Muhammad Nawaz; Amjad Hussain; Afroz Rais; Safia Gul; Danish Ibrar; Manzer H. Siddiqui; Abdel-Rhman Z. Gaafar; et al. (International Journal of Plant Production, 2024)

Modeling and monitoring cotton production using remote sensing techniques and machine learning: a case study of Punjab, Pakistan - Sher Shah Hasan; Muhammad Arif Goheer; Muhammad Uzair; Saba Fatima (Environment, Development and Sustainability, 2024)

Long-term raw crop residue but not burned residue incorporation improved soil multifunctionality in semi-arid agroecosystems - Aqeel Ahmad; Muhammad Saleem Arif; Sher Muhammad Shahzad; Tahira Yasmeen; Awais Shakoor; Shahid Iqbal; Asam Riaz; Anjum Zahid; Stephen James Chapman (Soil and Tillage Research, 2024)

Maleated Hydroxyethyl Cellulose for the Efficient Removal of Cd(II) Ions from an Aqueous Solution: Isothermal, Kinetic and Regeneration Studies - Fatima Khan; Abu Bakar Siddique; Muhammad Imran Irfan; Muhammad Naeem ul Hassan; Muhammad Sher; Hassan A. Alhazmi; Abdulrahman N. Qramish; Hatem M. A. Amin; Rahman Qadir; Azhar Abbas (Water, Air, & Soil Pollution, 2024)

Efficacy of activated carbon using Salvadora persica stem for remediation of potentially toxic dyes from aqueous solution - Muhammad Bilal; Wahid Ullah; Tahir Abbas; Javed Ali; Syed Shah Hassan; Esraa M. Bakhsh; Kalsoom Akhtar; Sher Bahadar Khan (Environmental Monitoring and Assessment, 2024)

Aflatoxins in the rice production chain: A review on prevalence, detection, and decontamination strategies - Iqra Naeem; Amir Ismail; Muhammad Riaz; Mubashir Aziz; Kashif Akram; Muhammad A. Shahzad; Mavra Ameen; Sher Ali; Carlos A.F. Oliveira (Food Research International, 2024)

Population exposure to emerging perfluoroalkyl acids (PFAAs) via drinking water resources: Application of multivariate statistics and risk assessment models - Kifayatullah Khan; Muhammad Younas; Jafar Ali; Noor Samad Shah; Yasar N. Kavil; Mohammed A. Assiri; Xianghui Cao; Hassan Sher; Afsheen Maryam; Yunqiao Zhou; Muhammad Yaseen; Li Xu (Marine Pollution Bulletin, 2024)

Comparative performance of osmotic and thermal driven anaerobic membrane bioreactors for hazardous textile wastewater treatment - Kamran Manzoor; Sher Jamal Khan; Muhammad Saqib Nawaz; Noreddine Ghaffour (Journal of Water Process Engineering, 2024)

Sunlight-assisted green synthesis of gold nanocubes using horsetail leaf extract: A highly selective colorimetric sensor for Pb2+, photocatalytic and antimicrobial agent - Abdul Waheed Khan; Naveed Shahzad Lali; Fahad Y. Sabei; Muhammad Imran Irfan; Muhammad Naeem-ul-Hassan; Muhammad Sher; Awaji Y. Safhi; Abdullah Alsalhi; Ahmed H. Albariqi; Faroq Kamli; Hatem M.A. Amin; Azhar Abbas (Journal of Environmental Chemical Engineering, 2024)

Silver oxide doped iron oxide/alginate nanocomposite coated cotton cloth for selective catalytic reduction of potassium ferricyanide - Esraa M. Bakhsh; Kalsoom Akhtar; Sher Bahadar Khan; Abdullah M. Asiri; Tahseen Kamal; Muhammad Bilal; Shahid Ali Khan (Chemosphere, 2024)

The therapeutic effect of BODIPY-based photosensitizers against acetylcholinesterase for the treatment of Alzheimer’s disease - Mushtaq Ahmed; Nadia Mushtaq; Naila Sher; Rahmat Ali Khan; Muhammad Amir Masood (Journal of Proteins and Proteomics, 2024)

Does no-till crop management mitigate gaseous emissions and reduce yield disparities: An empirical US-China evaluation - Awais Shakoor; Elise Pendall; Muhammad Saleem Arif; Taimoor Hassan Farooq; Shahid Iqbal; Sher Muhammad Shahzad (Science of The Total Environment, 2024)

Foliar application of 5-aminolevulinic acid improves the salt tolerance in sunflower (Helianthus annuus L.) by enhancing the morphological attributes and antioxidant defense mechanism - Ahmad Sher; Ahmad Nawaz; Sami Ul-Allah; Abdul Sattar; Muhammad Ijaz; Abdul Qayyum; Abdul Manaf (Acta Physiologiae Plantarum, 2024)

Kinetic & thermodynamic studies of green fuel additive solketal from crude glycerol over metakaolin clay catalyst - Imtisal Zahid; Muhammad Ayoub; Muhammad Hamza Nazir; Farooq Sher; Rashid Shamsuddin; Bawadi bin Abdullah; Mariam Ameen (Biomass and Bioenergy, 2024)

Development and testing of environment friendly nanohybrid coatings for sustainable agriculture technologies - Bilal Beig; Muhammad Bilal Khan Niazi; Farooq Sher; Zaib Jahan; Munir Zia; Ghulam Abbas Shah; Ayman A. Ghfar; Zahid Iqbal (Environmental Research, 2024)

Improved bio-oil yield from thermo-catalytic pyrolysis of Citrus limetta waste over pumice: Determination of kinetic parameters using Kissinger method - Faisal Muhammad; Jan Nisar; Ghulam Ali; Farooq Anwar; Syed Tasleem Hussain; Sher Wali Khan (Bioresource Technology Reports, 2023)

Balanced NPK Nutrition Improves Forage Productivity and Quality of Pearl Millet Grown in Semi-arid Regions of Pakistan - Ahmad Sher; Zahid Ali Akbar; Abdul Sattar; Sami Ul-Allah; Muhammad Ijaz; Roberta Calone; Lorenzo Barbanti (Journal of Soil Science and Plant Nutrition, 2023)

Exogenous Application of Silicon and Sulfate Improved Drought Tolerance in Sunflowers Through Modulation of Morpho-physiological and Antioxidant Defense Mechanisms - Muhammad Nisar; Muhammad Aqeel; Abdul Sattar; Ahmad Sher; Muhammad Ijaz; Sami Ul-Allah; Umair Rasheed; Salem Mesfir Al-Qahtani; Nadi Awad Al-Harbi; Fahad Mohammed Alzuaibr; Mohamed F. M. Ibrahim (Journal of Soil Science and Plant Nutrition, 2023)

A decline in snow cover area of Passu and Ghulkin valleys between 1995 and 2022 - Imran Hussain; Mumtaz Ali; Sher Muhammad; Wajid Hassan; Salar Ali; Zakir Hussain; Syed Hammad Ali; Shaukat Ali; Muhammad Younis Khan (Journal of Mountain Science, 2023)

Evaluating dye recovery and reusability potential from dyebath effluent using forward osmosis membranes for minimum liquid discharge - Maria Yasmeen; Muhammad Saqib Nawaz; Kamran Manzoor; Sher Jamal Khan; Noreddine Ghaffour (Chemosphere, 2023)

Biogenic silicon nanoparticles mitigate cadmium (Cd) toxicity in rapeseed (Brassica napus L.) by modulating the cellular oxidative stress metabolism and reducing Cd translocation - Temoor Ahmed; Hafiza Ayesha Masood; Muhammad Noman; Arwa Abdulkreem AL-Huqail; Suliman MS Alghanem; Muhammad Munem Khan; Sher Muhammad; Natasha Manzoor; Muhammad Rizwan; Xingjiang Qi; Amany H.A. Abeed; Bin Li (Journal of Hazardous Materials, 2023)

Arsenic fractionation and speciation in different textured soils supplied with farmyard manure and accumulation by sunflower under alkaline calcareous conditions - Muhammad Awais Piracha; Muhammad Ashraf; Sher Muhammad Shahzad; Sajid Masood; Naeem Akhtar; Rizwana Kausar; Awais Shakoor (Environmental Science and Pollution Research, 2023)

Unprecedented wildfires in Canada and transboundary effects of carbon monoxide pollution - Awais Shakoor; Taimoor Hassan Farooq; Muhammad Saleem Arif; Sher Muhammad Shahzad (Natural Hazards, 2023)

Improving Nitrogen Acquisition and Utilization Through Root Architecture Remodelling: Insight from Legumes - Muhammad Nadeem; Muhammad Yahya; Jingyang Tong; Liaqut Shah; Sana Ullah Khan; Ahmad Ali; Alam Sher; Najeeb Ullah; Abdul Waheed (Journal of Plant Growth Regulation, 2023)
In crop species, nutrient deficiency severely damages plant growth and developmental processes, leading to end-yield penalties. Root architecture remodelling is considered a key factor underpinning nutrient-poor soil environments. Adequate nitrogen (N) supply can play a significant role in sustaining crop productivity on nutrient-deficient soils. However, excessive application of nitrogenous fertilizer may pollute the soil and increase the production cost for the growers. To tackle this problem, crop breeders have made tremendous efforts to improve the N-use efficiency of agricultural crops. This article summarizes the recent progress in identifying QTLs/genes, regulatory pathways, and hormonal crosstalk involved in the growth and development of legumes roots system. Moreover, we have described the progress in microbe–root symbiosis via QTLs/genes regulations, which results in improved N acquisition. Understanding the molecular mechanisms that regulate the root architecture in response to N availability may help to strengthen the root system of legumes and promote environmental friendly and sustainable agriculture.

A modified experimental approach to determine formation porosity from rock cuttings - Semab Tariq; Zeeshan Khan; Allah Bakhsh; Syed Jamal ud Din; Azizullah Shaikh; Habib Ur Rehman; Rashid Sher Muhammad; Liang Zhang (Arabian Journal of Geosciences, 2023)

Composted Melia azedarach L. (Chinaberry tree) Sawdust Mixtures Regulate the Sprouting and Growth of Single Bud Node Seedlings of Sugarcane - Mehwish Sultan Ahmed; Muhammad Yasin; Muhammad Usman Zia; Muhammad Ather Nadeem; Sher Muhammad; Athar Mahmood (Journal of Soil Science and Plant Nutrition, 2023)

Optimum Zinc Fertilization and Sowing Date Improved Growth, Yield Components, and Grain Zn Contents of Bread Wheat Under Different Tillage Systems - Ijaz Hussain; Muhammad Ijaz; Sami Ul-Allah; Abdul Sattar; Ahmad Sher; Ahmad Nawaz; Abdul Ghaffar; Muhammad Habib ur Rahman; Saeed Ahmad; Iqra Rasheed; Omaima Nasif; Mohammad Javed Ansari (Journal of Soil Science and Plant Nutrition, 2023)

Modelling the impact of climate change on dengue outbreaks and future spatiotemporal shift in Pakistan - Alia Saeed; Shaukat Ali; Firdos Khan; Sher Muhammad; Michelle Simões Reboita; Abdul Wali Khan; Muhammad Arif Goheer; Mumtaz Ali Khan; Ramesh Kumar; Aamer Ikram; Aliya Jabeen; Sathirakorn Pongpanich (Environmental Geochemistry and Health, 2023)

Toxic effects of cadmium on the physiological and biochemical attributes of plants, and phytoremediation strategies: A review - Yanliang Li; Shafeeq Ur Rahman; Zhixin Qiu; Sher Muhammad Shahzad; Muhammad Farrakh Nawaz; Jianzhi Huang; Sadiq Naveed; Lei Li; Xiaojie Wang; Hefa Cheng (Environmental Pollution, 2023)

Exogenous application of melatonin alleviates the drought stress by regulating the antioxidant systems and sugar contents in sorghum seedlings - Ahmad Sher; Muhammad Umair Hassan; Abdul Sattar; Sami Ul-Allah; Muhammad Ijaz; Zara Hayyat; Yamin Bibi; Mubashar Hussain; Abdul Qayyum (Biochemical Systematics and Ecology, 2023)

Assessing drought and its impacts on wheat yield using remotely sensed observations in rainfed Potohar region of Pakistan - Muhammad Ijaz; Qudsia Zafar; Aftab Ahmad Khan; Sher Shah Hassan (Environment, Development and Sustainability, 2023)

Toward economic growth without emissions growth: the role of urbanization & industrialization in Pakistan - Sher Khan; Muhammad Tariq Majeed (Journal of Environmental Studies and Sciences, 2023)

Recovering and reuse of textile dyes from dyebath effluent using surfactant driven forward osmosis to achieve zero hazardous chemical discharge - Maria Yasmeen; Muhammad Saqib Nawaz; Sher Jamal Khan; Noreddine Ghaffour; Muhammad Zafar Khan (Water Research, 2023)

Efficient Regeneration in Sugarcane Using Thin Cell Layer (TCL) Culture System - Aneela Iqbal; Raham Sher Khan; Mubarak Ali Khan; Karim Gul; Muhammad Aizaz; Muhammad Usman; Muhammad Arif (Sugar Tech, 2023)

Assessment of climate change impacts on glacio-hydrological processes and their variations within critical zone - Muhammad Shafeeque; Yi Luo; Arfan Arshad; Sher Muhammad; Muhammad Ashraf; Quoc Bao Pham (Natural Hazards, 2023)

Bioinspired engineered nickel nanoparticles with multifunctional attributes for reproductive toxicity - Mehwish Iftikhar; Aasma Noureen; Farhat Jabeen; Muhammad Uzair; Nagina Rehman; Emina Karahmet Sher; Khadijah Mohammedsaleh Katubi; Juliana Heloisa Pinê Américo-Pinheiro; Farooq Sher (Chemosphere, 2023)

Renewable energy production from novel and non-edible seed oil of Cordia dichotoma using nickel oxide nano catalyst - Rozina; Mushtaq Ahmad; Nasib Qureshi; Muhammad Zafar; Sher Aman Ullah; Sheikh Zain Ul Abidin (Fuel, 2023)

Determining satellite-based evapotranspiration product and identifying relationship with other observed data in Punjab, Pakistan - Muhammad Amin; Mobushir Riaz Khan; Sher Shah Hassan; Muhammad Imran; Muhammad Hanif; Irfan Ahmad Baig (Environment, Development and Sustainability, 2023)

Occurrence and Distribution of Heavy Metals in Mining Degraded Soil and Medicinal Plants: A Case Study of Pb/Zn Sulfide Terrain Northern Areas, Pakistan - Javed Nawab; Muhammad Idress; Sajid Ullah; Gul Rukh; Rimsha Zainab; Hassan Sher; Junaid Ghani; Sardar Khan; Zahid Ullah; Imran Ahmad; Syed Weqas Ali (Bulletin of Environmental Contamination and Toxicology, 2023)

Wavelet coherence of monsoon and large‐scale climate variabilities with precipitation in Pakistan - Azfar Hussain; Jianhua Cao; Shaukat Ali; Waheed Ullah; Sher Muhammad; Ishtiaq Hussain; Haider Abbas; Kalpana Hamal; Shankar Sharma; Mobeen Akhtar; Xiuqin Wu; Jinxing Zhou (International Journal of Climatology, 2022)
Monsoon and its teleconnection with earth system internal processes affect the spatiotemporal distribution of precipitation and water resources . In this paper, the wavelet coherence analysis has been utilized, a time and frequency domain methodology for comparing the spectral features of two independent time series superior to linear approaches. This technique is used to capture the significant modes of variabilities in the Indian Summer Monsoon Index (ISMI) and large‐scale climate indices (CIs) between ocean–atmosphere oscillations, like Indian Ocean Dipole (IOD), El Niño–Southern Oscillation (ENSO), Pacific Decadal Oscillation (PDO), Southern Oscillation Index (SOI), North Atlantic Oscillation (NAO), Atlantic Multidecadal Oscillation (AMO), and Arctic Oscillation (AO) over Pakistan. Precipitation time series during 1960–2016 revealed significant interannual coherences with ISMI, whereas the remaining CIs (IOD, ENSO, PDO, SOI, NAO, AMO, and AO) revealed interannual, decadal and interdecadal coherences. However, AO revealed strongest coherences in R‐II, III, and VI at interdecadal scales among all CIs. Overall, the interannual cycles on ISMI are 2.8 years, IOD 1–5.3 years, PDO 0–5.3 years, SOI 1–5.3 years, NAO 0–5 years, AO 0–5 years, and AMO 0–8.3 years. Whereas, the remaining CIs shared interdecadal coherences over particular regions. The ISMI displayed coherences (except in the UIB) with the large‐scale CIs over various homogenous regions on an interannual scale. The dominant influence of ISMI is observed in R‐II and III; the significant coherences in R‐II ranged from ~8 to 32 months (~0.8–2.8 years). The IOD and NAO have major coherences than the remaining large‐scale CIs ranging from ~16 to 64 months (1.3–5.3 years). The AO has the most significant coherences observed in R‐II, III, and VI on the decadal/interdecadal scale from 128 months and above (almost 10–15 years). On a 1.0‐year timescale, all homogenous regions demonstrated strong intermittent coherence with ISMI, IOD, ENSO, PDO, SOI, NAO, AMO, and AO. These findings have substantial implications for decision‐makers and scientists in Pakistan looking to enhance water resource planning and operations in the face of future climate uncertainties.

Observed trends and variability of seasonal and annual precipitation in Pakistan during 1960–2016 - Azfar Hussain; Jianhua Cao; Shaukat Ali; Sher Muhammad; Waheed Ullah; Ishtiaq Hussain; Mobeen Akhtar; Xiuqin Wu; Yinghui Guan; Jinxing Zhou (International Journal of Climatology, 2022)
Long‐term precipitation monitoring plays a vital role in water resource management and disaster prevention and mitigation. This study assesses spatial and temporal trends in seasonal and annual precipitation in Pakistan between 1960 and 2016 at an interannual scale. The Mann–Kendall (MK) test, Sen's slope (SS) estimator, and Sequential Mann–Kendall (SQMK) test were employed to assess trends. Cluster analysis and L ‐moment approach were used to identify the homogenous precipitation regions. In general, increasing precipitation trends between 1960 and 2016 were evident. Results indicated increasing precipitation in winter, autumn, summer and annual scale at the rates of 0.20, 2.18, 5.16, and 10.89 mm·decade −1 , respectively. In spring, the precipitation trend shows a decreasing trend at −0.67 mm·decade −1 . Moreover, a significant decreasing trend occurred in winter in southern Pakistan. The overall increasing trends were more noticeable between 1960 and 1988, compared to the declining precipitation during 1989–2016. SQMK analysis indicates a clear downward trend in most regions during 1989–2016, except in autumn. Annual precipitation has increased topographically except at 500 m and 1,500 m during 1960–2016 with a significant increase of 1.37 mm·decade −1 at elevation

Contrasting treeline dynamics of pine and birch in response to climate warming in the Karakoram - Munawar Ali; Shalik Ram Sigdel; Xiangyu Zheng; Fayaz Asad; Ru Huang; Haifeng Zhu; Sher Muhammad; Iqtidar Hussain; Saulat Hussain; J. Julio Camarero; Eryuan Liang (Trees, 2022)

Combined Effect of Organic Amendments and Seed Placement Techniques on Sorghum Yield Under Salt-Stressed Conditions - Attaullah Khan; Aftab Ahmad Khan; Muhammad Jamal Khan; Muhammad Ijaz; Sher Shah Hassan (Journal of Soil Science and Plant Nutrition, 2022)

Spatio-temporal landslide inventory and susceptibility assessment using Sentinel-2 in the Himalayan mountainous region of Pakistan - Alam Sher Bacha; Muhammad Shafique; Harald van der Werff; Mark van der Meijde; Mian Luqman Hussain; Sohail Wahid (Environmental Monitoring and Assessment, 2022)

Mechanisms of β-adrenergic receptors agonists in mediating pro and anti-apoptotic pathways in hyperglycemic Müller cells - Sher Zaman Safi; Laiba Saeed; Humaira Shah; Zahina Latif; Abid Ali; Muhammad Imran; Nawshad Muhammad; Talha Bin Emran; Vetriselvan Subramaniyan; Ikram Shah Bin Ismail (Molecular Biology Reports, 2022)

Linking Plants Functioning to Adaptive Responses Under Heat Stress Conditions: A Mechanistic Review - Mahmood Ul Hassan; Tassaduq Rasool; Chandni Iqbal; Adnan Arshad; Muhammad Abrar; Muhammad Mohsin Abrar; Muhammad Habib-ur-Rahman; Mehmood Ali Noor; Alam Sher; Shah Fahad (Journal of Plant Growth Regulation, 2022)

Situational assessment for fecal sludge management in major cities of Pakistan - Nida Maqbool; Muhammad Arslan Shahid; Sher Jamal Khan (Environmental Science and Pollution Research, 2022)

Nanotechnology-based controlled release of sustainable fertilizers. A review - Bilal Beig; Muhammad Bilal Khan Niazi; Farooq Sher; Zaib Jahan; Umer Shahzad Malik; Mohammad Daud Khan; Juliana Heloisa Pinê Américo-Pinheiro; Dai-Viet N. Vo (Environmental Chemistry Letters, 2022)
The rising population is increasing food demand, yet actual crop production is limited by the poor efficiency of classical fertilizers. In particular, only about 40–60% of fertilizer nitrogen, 15–20% of phosphorus and 50–60% of potassium are used by crop plants, the rest ending polluting the environment. Nanofertilizers are promising alternatives. Here, we review plant nutrients, synthesis of zinc oxide nanoparticles, encapsulation of nanoparticles in fertilizers, and effect on plants.

The Effect of Selenium Concentration on the Quantitative and Qualitative Yield of Four Safflower (Carthamus tinctorius L.) Genotypes - Ahmad Sher; Sami Ul-Allah; Abdul Sattar; Muhammad Ijaz; Waqas Ahmad; Yamin Bibi; Abdul Qayyum (Journal of Soil Science and Plant Nutrition, 2022)

Exogenous application of strigolactone alleviates drought stress in maize seedlings by regulating the physiological and antioxidants defense mechanisms - Abdul Sattar; Sami Ul-Allah; Muhammad Ijaz; Ahmad Sher; Madiha Butt; Tahira Abbas; Muhammad Irfan; Tehreem Fatima; Saleh Alfarraj; Sulaiman Ali Alharbi (Cereal Research Communications, 2022)

Wetting mechanism and morphological adaptation; leaf rolling enhancing atmospheric water acquisition in wheat crop—a review - Zulfiqar Ali; Sabah Merrium; Muhammad Habib-ur-Rahman; Sadia Hakeem; Muhammad Abu Bakar Saddique; Muhammad Ali Sher (Environmental Science and Pollution Research, 2022)
Several plant species such as grasses are dominant in many habitats including arid and semi-arid areas. These species survive in these regions by developing exclusive structures, which helps in the collection of atmospheric water. Before the collected water evaporates, these structures have unique canopy structure for water transportation that plays an equivalent share in the fog-harvesting mechanism. In this review, the atmospheric gaseous water harvesting mechanisms and their affinity of measurements were discussed. Morphological adaptations and their role in the capturing of atmospheric gaseous water of various species were also discussed. The key factor for the water collection and its conduction in the wheat plant is the information of contact angle hysteresis. In wheat, leaf rolling and its association with wetting property help the plant in water retention. Morphological adaptations, i.e., leaf erectness, grooves, and prickle hairs, also help in the collection and acquisition of water droplets by stem flows in directional guide toward the base of the plant and allow its rapid uptake. Morphological adaptation strengthens the harvesting mechanism by preventing the loss of water through shattering. Thus, wheat canopy architecture can be modified to harvest the atmospheric water and directional movement of water towards the root zone for self-irrigation. Moreover, these morphological adaptations are also linked with drought avoidance and corresponding physiological processes to resist water stress. The combination of these traits together with water use efficiency in wheat contributes to a highly efficient atmospheric water harvesting system that enables the wheat plants to reduce the cost of production. It also increases the yielding potential of the crop in arid and semi-arid environments. Further investigating the ecophysiology and molecular pathways of these morphological adaptations in wheat may have significant applications in varying climatic scenarios.

Bio-diesel production of sunflower through sulphur management in a semi-arid subtropical environment - Athar Mahmood; Masood Iqbal Awan; Sana Sadaf; Ahmed Mukhtar; Xiukang Wang; Sajid Fiaz; Sher Aslam Khan; Habib Ali; Faran Muhammad; Zafar Hayat; Farhana Gul; Shah Fahad (Environmental Science and Pollution Research, 2022)

Spatial distribution of carbon dynamics and nutrient enrichment capacity in different layers and tree tissues of Castanopsis eyeri natural forest ecosystem - Taimoor Hassan Farooq; Xen Xincheng; Awais Shakoor; Muhammad Haroon U. Rashid; Muhammad Farhan Bashir; Muhammad Farrakh Nawaz; Uttam Kumar; Sher Muhammad Shahzad; Wende Yan (Environmental Science and Pollution Research, 2022)

Nano-structured dynamic Schiff base cues as robust self-healing polymers for biomedical and tissue engineering applications: a review - Umer Shahzad Malik; Muhammad Bilal Khan Niazi; Zaib Jahan; Mazhar Iqbal Zafar; Dai-Viet N. Vo; Farooq Sher (Environmental Chemistry Letters, 2022)
Polymer materials are vulnerable to damages, failures, and degradations, making them economically unreliable. Self-healing polymers, on the other hand, are multifunctional materials with superior properties of autonomic recovery from physical damages. These materials are suitable for biomedical and tissue engineering in terms of cost and durability. Schiff base linkages-based polymer materials are one of the robust techniques owing to their simple self-healing mechanism. These are dynamic reversible covalent bonds, easy to fabricate at mild conditions, and can self-reintegrate after network disruption at physiological conditions making them distinguished. Here we review self-healing polymer materials based on Schiff base bonds. We discuss the Schiff base bond formation between polymeric networks, which explains the self-healing phenomenon. These bonds have induced 100% recovery in optimal cases.

Foliar Spray of Natural and Synthetic Plant Growth Promoters Accelerates Growth and Yield of Cotton by Modulating Photosynthetic Pigments - Muhammad Shaukat; Ashfaq Ahmad; Tasneem Khaliq; Irfan Afzal; Sher Muhammad; Bushra Safdar; Sabir Hussain Shah (International Journal of Plant Production, 2021)

Decoupling and decomposition analysis of environmental impact from economic growth: a comparative analysis of Pakistan, India, and China - Ilhan Ozturk; Muhammad Tariq Majeed; Sher Khan (Environmental and Ecological Statistics, 2021)

Unprecedented Impacts of Aviation Emissions on Global Environmental and Climate Change Scenario - Farooq Sher; David Raore; Jiří Jaromír Klemeš; Piyya Muhammad Rafi-ul-Shan; Martin Khzouz; Kristina Marintseva; Omid Razmkhah (Current Pollution Reports, 2021)
There has been a continuously growing trend in international commercial air traffic, with the exception of COVID-19 crises; however, after the recovery, the trend is expected to even sharpen. The consequences of released emissions and by-products in the environment range from human health hazards, low air quality and global warming. This study is aimed to investigate the role of aviation emissions in global warming. For this purpose, data on different variables including global air traffic and growth rate, air traffic in different continents, total global CO 2 emissions of different airlines, direct and indirect emissions, air traffic in various UK airports and fuel-efficient aircraft was collected from various sources like EU member states, Statista, Eurostat, IATA, CAA and EUROCONTROL. The results indicated that in 2019, commercial airlines carried over 4.5 × 10 9 passengers on scheduled flights. However, due to the COVID-19 pandemic in 2020, the global number of passengers was reduced to 1.8 × 10 9 , representing around a 60% reduction in air traffic. Germany was the largest contributor to greenhouse gas (GHG) from the EU, releasing 927 kt of emissions in 3 years. In the UK, Heathrow airport had the highest number of passengers in 2019 with over 80 million, and the study of monthly aircraft movement revealed that Heathrow Airport also had the highest number of EU and International flights, while Edinburgh had the domestic flights in 2018. These research findings could be beneficial for airlines, policymakers and governments targeting the reduction of aircraft emissions. Graphical abstract

Environmental and human iodine and selenium status: lessons from Gilgit-Baltistan, North-East Pakistan - Saeed Ahmad; Elizabeth H. Bailey; Muhammad Arshad; Sher Ahmed; Michael J. Watts; Alex G. Stewart; Scott D. Young (Environmental Geochemistry and Health, 2021)
Iodine and selenium deficiencies are common worldwide. We assessed the iodine and selenium status of Gilgit-Baltistan, Pakistan. We determined the elemental composition (ICP-MS) of locally grown crops ( n = 281), drinking water ( n = 82), urine ( n = 451) and salt ( n = 76), correcting urinary analytes for hydration (creatinine, specific gravity). We estimated dietary iodine, selenium and salt intake. Median iodine and selenium concentrations were 11.5 (IQR 6.01, 23.2) and 8.81 (IQR 4.03, 27.6) µg/kg in crops and 0.24 (IQR 0.12, 0.72) and 0.27 (IQR 0.11, 0.46) µg/L in water, respectively. Median iodised salt iodine was 4.16 (IQR 2.99, 10.8) mg/kg. Population mean salt intake was 13.0 g/day. Population median urinary iodine (uncorrected 78 µg/L, specific gravity-corrected 83 µg/L) was below WHO guidelines; creatinine-corrected median was 114 µg/L but was unreliable. Daily selenium intake (from urinary selenium concentration) was below the EAR in the majority (46–90%) of individuals. Iodine and selenium concentrations in all crops were low, but no health-related environmental standards exist. Iodine concentration in iodised salt was below WHO-recommended minimum. Estimated population average salt intake was above WHO-recommended daily intake. Locally available food and drinking water together provide an estimated 49% and 72% of EAR for iodine (95 µg/day) and selenium (45 µg/day), respectively. Low environmental and dietary iodine and selenium place Gilgit-Baltistan residents at risk of iodine deficiency disorders despite using iodised salt. Specific gravity correction of urine analysis for hydration is more consistent than using creatinine. Health-relevant environmental standards for iodine and selenium are needed.

Multiple geochemical factors may cause iodine and selenium deficiency in Gilgit-Baltistan, Pakistan - Saeed Ahmad; Elizabeth H. Bailey; Muhammad Arshad; Sher Ahmed; Michael J. Watts; Scott D. Young (Environmental Geochemistry and Health, 2021)
Deficiencies of the micronutrients iodine and selenium are particularly prevalent where populations consume local agricultural produce grown on soils with low iodine and selenium availability. This study focussed on such an area, Gilgit-Baltistan in Pakistan, through a geochemical survey of iodine and selenium fractionation and speciation in irrigation water and arable soil. Iodine and selenium concentrations in water ranged from 0.01–1.79 µg L −1 to 0.016–2.09 µg L −1 , respectively, which are smaller than levels reported in similar mountainous areas in other parts of the world. Iodate and selenate were the dominant inorganic species in all water samples. Average concentrations of iodine and selenium in soil were 685 µg kg −1 and 209 µg kg −1 , respectively, much lower than global averages of 2600 and 400 µg kg −1 , respectively. The ‘reactive’ fractions (‘soluble’ and ‘adsorbed’) of iodine and selenium accounted for < 7% and < 5% of their total concentrations in soil. More than 90% of reactive iodine was organic; iodide was the main inorganic species. By contrast, 66.9 and 39.7% of ‘soluble’ and ‘adsorbed’ selenium, respectively, were present as organic species; inorganic selenium was mainly selenite. Very low distribution coefficients (kd = adsorbed/soluble; L kg −1 ) for iodine (1.07) and selenium (1.27) suggested minimal buffering of available iodine and selenium against leaching losses and plant uptake. These geochemical characteristics suggest low availability of iodine and selenium in Gilgit-Baltistan, which may be reflected in locally grown crops. However, further investigation is required to ascertain the status of iodine and selenium in the Gilgit-Baltistan food supply and population.

Silicon Alleviates Arsenic Toxicity in Maize Seedlings by Regulating Physiological and Antioxidant Defense Mechanisms - Muhammad Kashif; Abdul Sattar; Sami Ul-Allah; Ahmad Sher; Muhammad Ijaz; Madiha Butt; Abdul Qayyum (Journal of Soil Science and Plant Nutrition, 2021)

The nexus between meteorological parameters and COVID-19 pandemic: case of Islamabad, Pakistan - Abdul Rehman; Fatima Ashraf; Zeeshan Javed; Mudassar Hussain; Taimoor Hassan Farooq; Awais Shakoor; Sher Muhammad Shahzad (Environmental Sustainability, 2021)

Fate of selenium in biofortification of wheat on calcareous soil: an isotopic study - Saeed Ahmad; Elizabeth H. Bailey; Muhammad Arshad; Sher Ahmed; Michael J. Watts; Scott D. Young (Environmental Geochemistry and Health, 2021)
Selenium (Se) biofortification of staple cereal crops can improve the Se nutritional status of populations. A field trial employing an enriched stable isotope of Se ( 77 Se) was undertaken over three consecutive cropping seasons in a coarse-textured, calcareous soil in Gilgit-Baltistan, Pakistan. The objectives were to (1) assess the feasibility and efficiency of Se biofortification, (2) determine the fate of residual Se, and (3) assess the consequences for dietary Se intake. Isotopically enriched 77 Se ( 77 Se Fert ) was applied, either as selenate or as selenite, at three levels (0, 10, and 20 g ha −1 ) to a wheat crop. Residual 77 Se Fert availability was assessed in subsequent crops of maize and wheat without further 77 Se Fert addition. Loss of 77 Se Fert was c.35% by the first (wheat) harvest, for both selenium species, attributable to the practice of flood irrigation and low adsorption capacity of the soil. No 77 Se Fert was detectable in subsequent maize or wheat crops. The remaining 77 Se Fert in soil was almost entirely organically bound and diminished with time following a reversible (pseudo-)first-order trend. Thus, repeat applications of Se would be required to adequately biofortify grain each year. In contrast to native soil Se, there was no transfer of 77 Se Fert to a recalcitrant form. Grain from control plots would provide only 0.5 µg person −1 day −1 of Se. By contrast, a single application of 20 g ha −1 Se VI could provide c. 47 µg person −1 day −1 Se in wheat, sufficient to avoid deficiency when combined with dietary Se intake from other sources (c. 25 µg day −1 ).

HEC-RAS and GIS-based flood plain mapping: A case study of Narai Drain Peshawar - Awais Salman; Sher Shah Hassan; Gul Daraz Khan; Muhammad Arif Goheer; Aftab Ahmad Khan; Khurram Sheraz (Acta Geophysica, 2021)

Modeling and Monitoring Wheat Crop Yield Using Geospatial Techniques: A Case Study of Potohar Region, Pakistan - Sher Shah Hassan; Muhammad Arif Goheer (Journal of the Indian Society of Remote Sensing, 2021)

Tree-ring-based temperature reconstruction from the western Himalayan region in northern Pakistan since 1705 C.E. - Adam Khan; Moinuddin Ahmed; Narayan Prasad Gaire; Javed Iqbal; Muhammad Faheem Siddiqui; Afsheen Khan; Mohib Shah; Ali Hazrat; Najm Us Saqib; Wali Khan Mashwani; Sher Shah; Sanjaya Bhandari (Arabian Journal of Geosciences, 2021)

First report of white mould of potato caused by Sclerotinia sclerotiorum in Pakistan - Muhammad Waqar Alam; Abdul Rehman; Arif Malik; Saira Mehboob; Mubeen Sarwar; Sher Muhammad (Journal of Plant Pathology, 2021)

Impact of foreign direct investment, natural resources, renewable energy consumption, and economic growth on environmental degradation: evidence from BRICS, developing, developed and global countries - Bashir Muhammad; Muhammad Kamran Khan; Muhammad Imran Khan; Sher Khan (Environmental Science and Pollution Research, 2021)

Landslide inventory and susceptibility assessment using multiple statistical approaches along the Karakoram highway, northern Pakistan - Mian Luqman Hussain; Muhammad Shafique; Alam Sher Bacha; Xiao-qing Chen; Hua-yong Chen (Journal of Mountain Science, 2021)

Impact of financial development and energy consumption on environmental degradation in 184 countries using a dynamic panel model - Sher Khan; Muhammad Kamran Khan; Bashir Muhammad (Environmental Science and Pollution Research, 2021)

Variability and Predictability of Summer Monsoon Rainfall over Pakistan - Muhammad Adnan; Firdos Khan; Nadia Rehman; Shaukat Ali; Sher Shah Hassan; Muhammad Mubashar Dogar; Shahbaz Mehmood; Shabehul Hasson (Asia-Pacific Journal of Atmospheric Sciences, 2021)

Performance evaluation of participatory irrigation management as an alternative to a state‐managed irrigation system* - Sabir Hussain; Mudasser Muneer Khan; Muhammad Shoaib; Ali Raza; Syyed Adnan Raheel Shah; Tanveer Ahmed Khan; Sher Khan (Irrigation and Drainage, 2021)
The Lower Bari Doab Canal (LBDC) system is one of the large old irrigation systems in Punjab, Pakistan. To overcome problems of water distribution and management in conventional state‐managed irrigation, a participatory irrigation management (PIM) system was introduced in the LBDC command area in 2012. From the very large system of the LBDC, 20 different kinds of distributaries were selected in this study as representatives for evaluating performance of the new system. The primary data were gathered through questionnaires and by interviewing farmers, whereas the secondary data were gathered from the related offices of the Punjab Irrigation Department. The analysis of collected data illustrates that water service deliveries (WSDs) were poor even after implementation of PIM. The research shows that under administration of both systems, efficiency regarding provision of water seemed to be poor. The outcomes show that with the passage of time, recovery ( abiana ) decreased after implementation of the PIM system but the financial sustainability of PIM has improved compared to state administration. Finally, the current study recommends institutional reforms in PIM and comprehensive work on educating the farmers about their role in PIM as a mandatory component for improving efficiency of the PIM system.

Future climatic changes, extreme events, related uncertainties, and policy recommendations in the Hindu Kush sub-regions of Pakistan - Shaukat Ali; Alia Saeed; Rida Sehar Kiani; Sher Muhammad; Firdos Khan; Romaisa Babar; Asif Khan; Muhammad Shahid Iqbal; Muhammad Arif Goheer; Wajid Naseem; Shah Fahad (Theoretical and Applied Climatology, 2021)

Bioaccumulation of cadmium in different genotypes of wheat crops irrigated with different sources of water in agricultural regions - Asma Zafar; Zafar Iqbal Khan; Wuyi Liu; Humayun Bashir; Kafeel Ahmad; Kinza Wajid; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq; Muhammad Nadeem; Tasneem Ahmad; Ijaz Rasool Noorka; et al. (Environmental Science and Pollution Research, 2021)

Interactive Effect of Biochar and Silicon on Improving Morpho-Physiological and Biochemical Attributes of Maize by Reducing Drought Hazards - Abdul Sattar; Ahmad Sher; Muhammad Ijaz; Sami Ul-Allah; Madiha Butt; Muhammad Irfan; Muhammad Shahid Rizwan; Hakoomat Ali; Mumtaz A. Cheema (Journal of Soil Science and Plant Nutrition, 2020)

Heterologous expression of azoreductase-encoding gene azrS of Bacillus sp. MR-1/2 for enhanced azo dye decolorization and wastewater treatment - Ali Abbas; Aqsa Mushtaq; Ayesha Iftikhar Cheema; Faisal Mahmood; Muhammad Asaf Khan; Tahir Naqqash; Mohsin Khurshid; Irfan Manzoor; Sher Muhammad; Muhammad Shahid (Archives of Microbiology, 2020)

Foliage applied proline induces salt tolerance in chili genotypes by regulating photosynthetic attributes, ionic homeostasis, and antioxidant defense mechanisms - Madiha Butt; Abdul Sattar; Tahira Abbas; Ahmad Sher; Muhammad Ijaz; Sami Ul-Allah; Muhammad Rashid Shaheen; Fawad Kaleem (Horticulture, Environment, and Biotechnology, 2020)

Erratum to: Spatio-temporal changes in the six major glaciers of the Chitral River basin (Hindukush Region of Pakistan) between 2001 and 2018 - Jawaria Gul; Sher Muhammad; Shi-yin Liu; Siddique Ullah; Shakeel Ahmad; Huma Hayat; Adnan Ahmad Tahir (Journal of Mountain Science, 2020)
The article Spatio-temporal changes in the six major glaciers of the Chitral River basin (Hindukush Region of Pakistan) between 2001 and 2018, written by Jawaria GUL, Sher MUHAMMAD, LIU Shi-yin, Siddique ULLAH, Shakeel AHMAD, Huma HAYAT and Adnan Ahmad TAHIR, was originally published Online First without Open Access. After publication in volume 17, issue 3, page 572-587, the author decided to opt for Open Choice and to make the article an Open Access publication. Therefore, the copyright of the article has been changed to © The Author(s) 2020 and the article is forthwith distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/), which permits use, duplication, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license, and indicate if changes were made. The original version of this article has been revised due to a retrospective Open Access order.

Transferability of object-based image analysis approaches for landslide detection in the Himalaya Mountains of northern Pakistan - Alam Sher Bacha; Harald Van Der Werff; Muhammad Shafique; Hawas Khan (International Journal of Remote Sensing, 2020)

ASTER-based remote sensing investigation of gypsum in the Kohat Plateau, north Pakistan - Asad Khan; Shah Faisal; Muhammad Shafique; Saad Khan; Alam Sher Bacha (Carbonates and Evaporites, 2020)

Spatio-temporal changes in the six major glaciers of the Chitral River basin (Hindukush Region of Pakistan) between 2001 and 2018 - Jawaria Gul; Sher Muhammad; Shi-yin Liu; Siddique Ullah; Shakeel Ahmad; Huma Hayat; Adnan Ahmad Tahir (Journal of Mountain Science, 2020)
Glaciers in the northern Pakistan are a distinctive source of freshwater for the irrigation, drinking and industrial water supplies of the people living in those regions and downstream. These glaciers are under a direct global warming impact as indicated in many previous studies. In this study, we estimated the glacier dynamics in terms of Equilibrium Line Altitude (ELA), mass balance and the snout position variation using remote sensing data between 2001 and 2018. Six glaciers, having area ≥ 20 km 2 each, situated in the Chitral region (Hindukush Mountains) were investigated in this study. Digital Elevation Model (DEM) and available cloud-free continuous series of Landsat and Sentinel the entire study area was a retreat of -231 ± 140 m. No obvious relationship was found between the glacier variation trends and the available gauged climatic data possibly due to the presence of debris cover in ablation zones of all the studied glaciers which provides insulation and reduces the immediate climatic effects.

Spatial analysis of temperature time series over the Upper Indus Basin (UIB) Pakistan - Yasir Latif; Ma Yaoming; Muhammad Yaseen; Sher Muhammad; Muhammad Atif Wazir (Theoretical and Applied Climatology, 2020)
Runoff generated from the Upper Indus Basin (UIB) mainly originates in the massifs of the Hindukush–Karakoram–Himalaya (HKH) region of Pakistan. Water supply in early spring depends upon the snow accumulation in the winter and the subsequent temperature. Seasonal temperature variations corroborate the contemporary dynamics of snow and glaciers. Recently, there has been increasing evidence of accelerated warming in high mountain areas, termed as elevation-dependent warming (EDW). We have identified trends, analyzed inconsistencies, and calculated changes in the maximum, minimum, mean and diurnal temperature range ( T max , T min , T mean , and DTR) at 20 weather stations during four-time series: 1961–2013 (first), 1971–2013 (second), 1981–2013 (third), and 1991–2013 (fourth). We employed the Mann–Kendall test to determine the existence of a trend and Sen’s method for the estimation of prevailing trends, whereas homogeneity analysis was applied before trend identification using three different tests. This study revealed that the largest and smallest magnitudes of trends appeared in the winter and summer, respectively, particularly during the fourth data series. T max revealed robust warming at ten stations, most remarkably at Gupis, Khunjrab, and Naltar at rates of 0.29, 0.36, and 0.43 °C/decade, respectively, during the fourth series. We observed that T min exhibits a mixed pattern of warming and cooling during the second and third series, but cooling becomes stronger during the fourth series, exhibiting significant trends at twelve stations. Khunjrab and Naltar showed steady warming during the fourth series (spring), at rates of 0.26 and 0.13 °C/decade in terms of T mean . The observed decreases in DTR appeared stronger in the fourth series during the summer. These findings tend to partially support the notion of EDW but validate the dominance of cooling spatially and temporally.

Supplemental potassium mediates antioxidant metabolism, physiological processes, and osmoregulation to confer salt stress tolerance in cabbage (Brassica oleracea L.) - Waqas Ahmad; Chaudhary Muhammad Ayyub; Muhammad Asif Shehzad; Khurram Ziaf; Muhammad Ijaz; Ahmad Sher; Tahira Abbas; Jamil Shafi (Horticulture, Environment, and Biotechnology, 2019)

Heat treatment effects on chilling injury and disease incidence in sweet orange fruits stored at chilling and non-chilling temperatures - Ijaz Hussain; Abdur Rab; Naqib Ullah Khan; Zarina Bibi; Shah Masaud Khan; Naushad Ali; Muhammad Saeed; Sher Aslam Khan; Sardar Ali; Ghulam Dastagir; Muhammad Sajid (Journal of Consumer Protection and Food Safety, 2019)

Interactive Effect of Zinc Fertilization and Cultivar on Yield and Nutritional Attributes of Canola (Brassica napus L.) - Abdul Manaf; Muhammad Raheel; Ahmad Sher; Abdul Sattar; Sami Ul-Allah; Abdul Qayyum; Qaisar Hussain (Journal of Soil Science and Plant Nutrition, 2019)

Physiological and biochemical attributes of bread wheat (Triticum aestivum L.) seedlings are influenced by foliar application of silicon and selenium under water deficit - Abdul Sattar; Mumtaz Akhtar Cheema; Ahmad Sher; Muhammad Ijaz; Sami Ul-Allah; Ahmad Nawaz; Tahira Abbas; Qasim Ali (Acta Physiologiae Plantarum, 2019)

Sewage waste water application improves the productivity of diverse wheat (Triticum aestivum L.) cultivars on a sandy loam soil - Muhammad Ijaz; Abdul Waheed; Sami Ul-Allah; Ahmad Nawaz; Allah Wasaya; Abdul Sattar; Ahmad Sher (Environmental Science and Pollution Research, 2019)

Evaluation of Potential Toxic Metals Accumulation in Wheat Irrigated with Wastewater - Kafeel Ahmad; Kinza Wajid; Zafar Iqbal Khan; Ilker Ugulu; Hafsa Memoona; Madiha Sana; Khalid Nawaz; Ifra Saleem Malik; Humayun Bashir; Muhammad Sher (Bulletin of Environmental Contamination and Toxicology, 2019)

Influence of different organic geo-sorbents on Spinacia oleracea grown in chromite mine-degraded soil: a greenhouse study - Javed Nawab; Nayab Khan; Riaz Ahmed; Sardar Khan; Junaid Ghani; Ziaur Rahman; Fawad Khan; Xiaoping Wang; Juma Muhammad; Hassan Sher (Journal of Soils and Sediments, 2019)

Toxicological potential of cobalt in forage for ruminants grown in polluted soil: a health risk assessment from trace metal pollution for livestock - Zafar Iqbal Khan; Nimra Arshad; Kafeel Ahmad; Muhammad Nadeem; Asma Ashfaq; Kinza Wajid; Humayun Bashir; Mudasra Munir; Bushra Huma; Hafsa Memoona; Madiha Sana; Khalid Nawaz; et al. (Environmental Science and Pollution Research, 2019)

Combined application of biochar and PGPR consortia for sustainable production of wheat under semiarid conditions with a reduced dose of synthetic fertilizer - Muhammad Ijaz; Muhammad Tahir; Muhammad Shahid; Sami Ul-Allah; Abdul Sattar; Ahmad Sher; Khalid Mahmood; Mubshar Hussain (Brazilian Journal of Microbiology, 2019)

Input Selection of Wavelet-Coupled Neural Network Models for Rainfall-Runoff Modelling - Muhammad Shoaib; Asaad Y. Shamseldin; Sher Khan; Muhammad Sultan; Fiaz Ahmad; Tahir Sultan; Zakir Hussain Dahri; Irfan Ali (Water Resources Management, 2019)

iNuc-ext-PseTNC: an efficient ensemble model for identification of nucleosome positioning by extending the concept of Chou’s PseAAC to pseudo-tri-nucleotide composition - Muhammad Tahir; Maqsood Hayat; Sher Afzal Khan (Molecular Genetics and Genomics, 2019)

Assessment of Trace Metal and Metalloid Accumulation and Human Health Risk from Vegetables Consumption through Spinach and Coriander Specimens Irrigated with Wastewater - Zafar Iqbal Khan; Ilker Ugulu; Kafeel Ahmad; Sumaira Yasmeen; Ijaz Rasool Noorka; Naunain Mehmood; Muhammad Sher (Bulletin of Environmental Contamination and Toxicology, 2018)

Novel candidate genes and variants underlying autosomal recessive neurodevelopmental disorders with intellectual disability - Regie Lyn P. Santos-Cortez; Valeed Khan; Falak Sher Khan; Zaib-un-Nisa Mughal; Imen Chakchouk; Kwanghyuk Lee; Memoona Rasheed; Rifat Hamza; Anushree Acharya; Ehsan Ullah; Muhammad Arif Nadeem Saqib; Izoduwa Abbe; et al. (Human Genetics, 2018)

Landslide inventory and susceptibility modelling using geospatial tools, in Hunza-Nagar valley, northern Pakistan - Alam Sher Bacha; Muhammad Shafique; Harald van der Werff (Journal of Mountain Science, 2018)

Ridge sowing of sunflower (Helianthus annuus L.) in a minimum till system improves the productivity, oil quality, and profitability on a sandy loam soil under an arid climate - Ahmad Sher; Muhammad Suleman; Abdul Qayyum; Abdul Sattar; Allah Wasaya; Muhammad Ijaz; Ahmad Nawaz (Environmental Science and Pollution Research, 2018)

Biodegradation of plastics: current scenario and future prospects for environmental safety - Temoor Ahmed; Muhammad Shahid; Farrukh Azeem; Ijaz Rasul; Asad Ali Shah; Muhammad Noman; Amir Hameed; Natasha Manzoor; Irfan Manzoor; Sher Muhammad (Environmental Science and Pollution Research, 2018)

Phytochemical composition, biological potential and enzyme inhibition activity of Scandix pecten-veneris L. - Abdul Wahab; Syed Aleem Jan; Abdur Rauf; Zia ur Rehman; Zahid Khan; Aftab Ahmed; Fatima Syed; Sher Zaman Safi; Hamayun Khan; Muhammad Imran (Journal of Zhejiang University-SCIENCE B, 2018)

A Comparative Study of Various Hybrid Wavelet Feedforward Neural Network Models for Runoff Forecasting - Muhammad Shoaib; Asaad Y. Shamseldin; Sher Khan; Mudasser Muneer Khan; Zahid Mahmood Khan; Tahir Sultan; Bruce W. Melville (Water Resources Management, 2018)

A wavelet based approach for combining the outputs of different rainfall–runoff models - Muhammad Shoaib; Asaad Y. Shamseldin; Sher Khan; Mudasser Muneer Khan; Zahid Mahmood Khan; Bruce W. Melville (Stochastic Environmental Research and Risk Assessment, 2018)

Potentially Toxic Metals and Biological Contamination in Drinking Water Sources in Chromite Mining-Impacted Areas of Pakistan: A Comparative Study - Javed Nawab; Sardar Khan; Muhammad Amjad Khan; Hassan Sher; Ubaid Ur Rehamn; Sharafat Ali; Syed Mehboob Shah (Exposure and Health, 2017)

Phosphate-arsenate relations to affect arsenic concentration in plant tissues, growth, and antioxidant efficiency of sunflower (Helianthus annuus L.) under arsenic stress - Waqas Azeem; Muhammad Ashraf; Sher Muhammad Shahzad; Muhammad Imtiaz; Mumtaz Akhtar; Muhammad Shahid Rizwan (Environmental Science and Pollution Research, 2017)

Using Landsat images to monitor changes in the snow-covered area of selected glaciers in northern Pakistan - Chaman Gul; Shi-chang Kang; Badar Ghauri; Mateeul Haq; Sher Muhammad; Shaukat Ali (Journal of Mountain Science, 2017)

Exogenous silicon application alleviates salt stress in okra - Tahira Abbas; Abdul Sattar; Muhammad Ijaz; Muhammad Aatif; Samina Khalid; Ahmad Sher (Horticulture, Environment, and Biotechnology, 2017)

Response of cotton genotypes to water and heat stress: from field to genes - Muhammad Iqbal; Sami Ul-Allah; Muhammad Naeem; Muhammad Ijaz; Abdul Sattar; Ahmad Sher (Euphytica, 2017)

Retraction Note to: Estimation of Anticipated Performance Index and Air Pollution Tolerance Index and of vegetation around the marble industrial areas of Potwar region: bioindicators of plant pollution response - Mehwish Jamil Noor; Shazia Sultana; Sonia Fatima; Mushtaq Ahmad; Muhammad Zafar; Maliha Sarfraz; Masour A. Balkhyour; Sher Zaman Safi; Muhammad Aqeel Ashraf (Environmental Geochemistry and Health, 2017)

Are Karakoram temperatures out of phase compared to hemispheric trends? - Fayaz Asad; Haifeng Zhu; Hui Zhang; Eryuan Liang; Sher Muhammad; Suhaib Bin Farhan; Iqtidar Hussain; Muhammad Atif Wazir; Moinuddin Ahmed; Jan Esper (Climate Dynamics, 2017)

Low C/N ratio raw textile wastewater reduced labile C and enhanced organic-inorganic N and enzymatic activities in a semiarid alkaline soil - Mahnaz Roohi; Muhammad Riaz; Muhammad Saleem Arif; Sher Muhammad Shahzad; Tahira Yasmeen; Muhammad Arslan Ashraf; Muhammad Atif Riaz; Ishaq A. Mian (Environmental Science and Pollution Research, 2017)

Ameliorative effect of synthetic γ-aminobutyric acid (GABA) on performance traits, antioxidant status and immune response in broiler exposed to cyclic heat stress - Naila Chand; Sher Muhammad; Rifat Ullah Khan; Ibrahim Abdullah Alhidary; Zia ur Rehman (Environmental Science and Pollution Research, 2016)

Health risk assessment from contaminated foodstuffs: a field study in chromite mining-affected areas northern Pakistan - Javed Nawab; Gang Li; Sardar Khan; Hassan Sher; Muhammad Aamir; Isha Shamshad; Anwarzeb Khan; Muhammad Amjad Khan (Environmental Science and Pollution Research, 2016)

Benzamide sulfonamide derivatives: potent inhibitors of carbonic anhydrase-II - Muhammad Saleem; Aamer Saeed; Atia-tul-Wahab; Ajmal Khan; Sanaullah Abbasi; Waqasuddin Khan; Sher Bahadar Khan; M. Iqbal Choudhary (Medicinal Chemistry Research, 2016)

Contrasting effects of untreated textile wastewater onto the soil available nitrogen-phosphorus and enzymatic activities in aridisol - Muhammad Saleem Arif; Muhammad Riaz; Sher Muhammad Shahzad; Tahira Yasmeen; Alexandre Buttler; Juan Carlos Garcıa-Gil; Mahnaz Roohi; Akhtar Rasool (Environmental Monitoring and Assessment, 2016)

Comparative Assessment of Synthetic-derived and Conventional Bread Wheat Advanced Lines Under Osmotic Stress and Implications for Molecular Analysis - Ahmad Ali; Muhammad Arshad; S. M. Saqlan Naqvi; Awais Rasheed; Hassan Sher; Alvina Gul Kazi; Abdul Mujeeb-Kazi (Plant Molecular Biology Reporter, 2015)

Spatial distribution of pollutant emissions from crop residue burning in the Punjab and Sindh provinces of Pakistan: uncertainties and challenges - Muhammad Irfan; Muhammad Riaz; Muhammad Saleem Arif; Sher Muhammad Shahzad; Sabir Hussain; Muhammad Javed Akhtar; Leon van den Berg; Farhat Abbas (Environmental Science and Pollution Research, 2015)

Mapping of a new stem rust resistance gene Sr49 in chromosome 5B of wheat - Urmil K. Bansal; Sher Muhammad; Kerrie L. Forrest; Matthew J. Hayden; Harbans S. Bariana (Theoretical and Applied Genetics, 2015)

Mutation of ATF6 causes autosomal recessive achromatopsia - Muhammad Ansar; Regie Lyn P. Santos-Cortez; Muhammad Arif Nadeem Saqib; Fareeha Zulfiqar; Kwanghyuk Lee; Naeem Mahmood Ashraf; Ehsan Ullah; Xin Wang; Sundus Sajid; Falak Sher Khan; Muhammad Amin-ud-Din; Joshua D. Smith; et al. (Human Genetics, 2015)

Structural styles, hydrocarbon prospects, and potential in the Salt Range and Potwar Plateau, north Pakistan - Ishtiaq A. K. Jadoon; Matthias Hinderer; Beenish Wazir; Rizwan Yousaf; Sher Bahadar; Muhammad Hassan; Zeeshan-ul-Hassan Abbasi; Sidra Jadoon (Arabian Journal of Geosciences, 2015)

RETRACTED ARTICLE: Estimation of Anticipated Performance Index and Air Pollution Tolerance Index and of vegetation around the marble industrial areas of Potwar region: bioindicators of plant pollution response - Mehwish Jamil Noor; Shazia Sultana; Sonia Fatima; Mushtaq Ahmad; Muhammad Zafar; Maliha Sarfraz; Masour A. Balkhyour; Sher Zaman Safi; Muhammad Aqeel Ashraf (Environmental Geochemistry and Health, 2015)

Exploitation of synthetic-derived wheats through osmotic stress responses for drought tolerance improvement - Ahmad Ali; Muhammad Arshad; S. M. Saqlan Naqvi; Manzoor Ahmad; Hassan Sher; Sammer Fatima; Alvina Gul Kazi; Awais Rasheed; Abdul Mujeeb-Kazi (Acta Physiologiae Plantarum, 2014)

Co-inoculation integrated with P-enriched compost improved nodulation and growth of Chickpea (Cicer arietinum L.) under irrigated and rainfed farming systems - Sher Muhammad Shahzad; Azeem Khalid; Muhammad Saleem Arif; Muhammad Riaz; Muhammad Ashraf; Zafar Iqbal; Tahira Yasmeen (Biology and Fertility of Soils, 2014)

Effect of management on reproductive performances of the Achai cattle in the Hindu Kush (Northern Pakistan) - Muhammad Saleem; Inam-ur Rahim; Henri Rueff; Momen Khan; Daniel Maselli; Urs Wiesmann; Sher Muhammad (Tropical Animal Health and Production, 2012)

Assessment of Molybdenum Status in Soil and Forage for Ruminant Production Under Semiarid Environmental Conditions in Sargodha, Pakistan - Zafar Iqbal Khan; Kafeel Ahmad; Muhammad Ashraf; Nasra Raza; Muhammad Sher (Biological Trace Element Research, 2011)

Heterologous expression of a gene for thermostable xylanase from Chaetomium thermophilum in Pichia pastoris GS115 - Abdul Ghaffar; Sher Afzal Khan; Zahid Mukhtar; Muhammad Ibrahim Rajoka; Farooq Latif (Molecular Biology Reports, 2011)

In Vitro Distribution of Gold in Serum Proteins after Incubation of Sodium Aurothiomalate and Auranofin with Human Blood and its Pharmacological Significance - Mohammad S. Iqbal; Syed G. Taqi; Muhammad Arif; Muhammad Wasim; Muhammad Sher (Biological Trace Element Research, 2009)

Pharmacokinetic Study of Copper (II) Acetylsalicylate - Mohammad S. Iqbal; Muhammad Sher; Humayun Pervez; Maryiam Saeed (Biological Trace Element Research, 2008)

Quantitative estimation of dust fall and smoke particles in Quetta Valley - Muhammad Sami; Amir Waseem; Sher Akbar (Journal of Zhejiang University-SCIENCE B, 2006)

Phenolic constituents from Perovskia atriplicifolia - Shagufta Perveen; Sher Bahadar Khan; Abdul Malik; Rasool Bakhsh Tareen; Sarfraz Ahmad Nawaz; Muhammad Iqbal Choudhary (Natural Product Research, 2006)